Towards Co-existence. Responsibility in the Anthropocene Debate - Szyndler, Jeremiasz (Problemy Ekorozwoju, 2022)
P. Crutzen and E. Stoermer’s concept that humanity has entered a new geological epoch – the Anthropocene, in which the human species has become the leading geological force, is the subject of multidisciplinary scientific research. The debate on the Age of Man reconnects the sphere of facts and the normative sphere, while still continuing the eco-developmental concept oriented towards the search for new socio-economic solutions. One of the assumptions of the naturalistic narrative of the Anthropocene is the conviction that human action has the greatest impact on the environment and we are responsible for its condition. Often compared in literature to other great revolutions in science – Copernicus‘ and Darwin‘s theory – the paradigm shift in thinking in the Anthropocene  forces us to rethink the key concepts of classical philosophy: human, nature, responsibility. The article presents an outline of the ethical debate on responsibility in the Anthropocene, considering its collective and individual aspects, and introduces a new concept of co-existence, which integrates ecosystems with the technosphere. Koncepcja P. Crutzena i E. Stoermera sugerująca, że ludzkość wkroczyła w nową epokę geologiczną – antropocen, w której gatunek ludzki stał się wiodącą siłą geologiczną, jest przedmiotem multidyscyplinarnych badań naukowych. Debata nad Epoką Człowieka ponownie łączy sferę faktów ze sferą normatywną, kontynuując jednocześnie koncepcję ekorozwojową zorientowaną na poszukiwanie nowych rozwiązań społeczno-ekonomicznych. Jednym z założeń naturalistycznej narracji antropocenu jest przekonanie, że działalność człowieka ma największy wpływ na środowisko i to my jesteśmy odpowiedzialni za jego stan. Często porównywana w literaturze do innych wielkich rewolucji w nauce – teorii Kopernika i Darwina – zmiana paradygmatu myślenia w epoce antropocenu zmusza nas do ponownego przemyślenia kluczowych pojęć filozofii klasycznej: człowieka, natury, odpowiedzialności. Artykuł przedstawia zarys debaty etycznej na temat odpowiedzialności w antropocenie, z uwzględnieniem jej aspektów zbiorowych i indywidualnych, oraz wprowadza nową koncepcję współistnienia, integrującą ekosystemy z technosferą.